Does ex-ante disclosure of regulatory information really backfire? - Huiyang Zhou; Jian Chu (China Journal of Accounting Research)
Regulatory information disclosure is an important measure to enhance government transparency and law enforcement credibility. Studies mainly focus on ex-post disclosure and affirm its positive effects. However, ex-ante disclosure of regulatory information, as a representative regulatory policy, not only receives little attention in research but also is highly controversial in practice. This paper leverages the differential timing of disclosure of on-site inspections by the China Securities Regulatory Commission as the research setting to examine the impact of ex-ante disclosure of regulatory information on the governance of regulated listed companies. We find that ex-ante disclosure of regulatory information does not weaken the regulatory effect as expected, but rather enhances the governance of listed companies, as evidenced by the improvement of internal control quality. Mechanism analysis shows that ex-ante disclosure of regulatory information can stimulate shareholder activism and motivate investors to participate in corporate governance activities by exercising their rights and voicing their opinions, which in turn improves corporate governance. In addition, the heterogeneity test finds that regulatory capture induced by political connections weakens the governance effect of ex-ante disclosure of regulatory information. The economic consequence test shows that ex-ante disclosure of regulatory information reduces corporate violations and improves firm performance. Our findings suggest that ex-ante disclosure of regulatory information can mobilize investors, especially minority shareholders, to participate in corporate governance and promote the high-quality development of listed companies in a market-oriented way. Meanwhile, the institutional cost of regulatory capture stemming from ex-ante disclosure must be watchfully monitored.